Synthesis and characterization of metallapentalenoxazetes by the [2+2] cycloaddition of metallapentalynes with nitrosoarenes. Issue 44 (14th May 2019) - Deng, Zhihong; Zhu, Congqing; Hua, Yuhui; He, Guomei; Guo, Ying; Lu, Ruqiang; Cao, Xiaoyu; Chen, Jiangxi; Xia, Haiping
Abstract : The cycloaddition of metallapentalynes with nitrosoarenes produces metallapentalenoxazetes, in which two unstable frameworks are stabilized with a metal fragment. Abstract : Cycloaddition reactions of carbynes in metallacycles with π-bond substrates have been rarely reported. We report the first [2+2] cycloaddition of metallapentalynes with nitrosoarenes to obtain the first metallapentalenoxazetes, and their photophysical and electrochemical properties were studied by UV-Vis spectroscopy and cyclic voltammetry with the help of theoretical calculations.